Peran Komite Sekolah dalam Meningkatkan Pendidikan Masyarakat melalui Optimalisasi Dana BOS Kinerja di Kabupaten Buton Tengah - Suyati, Suyati; Wandira, Ayu; Hasanudin, Irpan; Hikmatiah, Waode; Tania, Nuril (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study examines the strategic role of school committees in optimizing the use of Performance-Based School Operational Assistance (BOS Kinerja) funds to strengthen community education in Buton Tengah Regency, Indonesia. The research was motivated by limited community participation and the need for transparent fund management in local schools. The objective is to analyze how school committees contribute to participatory governance, transparency, and educational empowerment. A descriptive qualitative method was applied, involving purposive selection of five elementary and junior high schools receiving BOS Kinerja. Data were collected through in-depth interviews with school principals, treasurers, and committee members, supported by direct observation and document analysis. The findings indicate that active school committees enhance the effectiveness of fund allocation by ensuring participatory planning, promoting transparency, and facilitating collaboration between schools and communities. Committees also support community-based programs such as parenting classes, literacy initiatives, and skills training, which broaden the role of schools as centers of community education. The study concludes that strengthening school committee capacity and institutionalizing their involvement throughout the BOS management cycle are essential for improving accountability and building inclusive, community-driven education governance.